Relationship between knowledge, attitude and practice of adults to the National Health Insurance Scheme and their health seeking behaviour in Unguwar soya, Kabong ward of Jos north LGA, Plateau state-Nigeria - Anthony, Ebenezer C.; Abner, Jemima; Adediran, Bukunmi T.; Ogundeko, Timothy O.; Bassi, Amos P.; Ramyl, Crown M. S. (International Journal Of Community Medicine And Public Health, 2022)
Background: Health seeking behaviour includes all those behaviour associated with establishing and retaining a healthy state, plus aspects of dealing with the departure from that state, which can generally be improved by health care financing and insurance. The objective of the study was to evaluate the knowledge, attitude and practice of National Health Insurance Scheme (NHIS) of the people of Unguwar soya community and its relationship to their health seeking behaviour. Methods: The study one was a cross sectional community based descriptive study carried out using a multi stage sampling process in Unguwar soya community, Plateau state, Nigeria. An interviewer administered structured questionnaire was utilized and administered to 252 eligible respondents for a period of 3 months (September-November, 2019). Results: Majority of the respondents were aged 20-29 years (33.7%), females (63.5%), with majority earning above 30,000 naira (25.8%). Most respondents (59.5%) had heard about NHIIS. Most (70.7%) had good attitude towards NHIS and had the desire to enroll under NHIS (70.3%), mostly because of Subsidization of health care cost. Only 13.3% of the respondents are registered with NHIS. The most of the population visit chemist shops when ill (31.2%), however, majority of NHIS enrollees go to hospitals to seek care. None of those enrolled go to health centers, pharmacies, and home of health workers. 90.1% agreed that their health seeking behaviour will improve if enrolled under NHIS. Conclusions: Index population has inadequate awareness and low practice of the NHIS also with long run impact on the health seeking behaviour of residents of Unguwar soya community.